«Восточные» зеркала-погремушки и бронзовые диски с гравировками - Шульга, П.И.; Оборин, Ю.В. (Археологія і давня історія України, 2017)
В 2014 г. в низовьях Оби у Полярного круга обнаружен богатый клад, в состав которого входило
нескольких крупных бронзовых дисков, очень похожих на рельефные оборотные диски зеркал-погремушек, до этого встречавшихся только в женских погребениях V—IV вв. до н. э. на Алтае, Верхнем
Приобье и Южном Урале в пазырыкской, каменской и прохоровской культурах. В ходе их изучения
установлено, что это впервые зафиксированная
особая категория культовых изделий. У 2014 р. в пониззі Обі біля Полярного кола був
виявлений багатий скарб, до складу якого входило
кілька великих бронзових дисків, дуже схожих на
рельєфні оборотні диски дзеркал-брязкалець, які
до цього зустрічалися тільки у жіночих похованнях
V—III ст. до н. е. на Алтаї, Верхньому Приоб'ї та
Південному Уралі у пазирикській, кам'янській та
прохорівській культурах. В ході вивчення зазначених бронзових дисків встановлено, що це не частина складових дзеркал-брязкалець, а вперше зафіксована особлива категорія культових виробів. In 2014 in lower reaches of the Ob River near the
Arctic Circle it was found a rich treasure which contained
a few large bronze discs very similar to some
large sculptured rattle-mirrors reverse disks earlier
found only in 4—3 centuries BC. female burials in Altai,
the Upper Ob Region and the southern Urals in
Pazyryk, Kamenskaya and Prokhorovskaya cultures.
In the study of these bronze discs it is found that is not
the part of composite rattle-mirrors but first recorded
special category of religious artifacts. On three copies
not found in Scythian-Siberian art mythical horses engraved
images preserved. Supposedly, these discs could
be produced in the III cent. BC. in some Near Eastern
handicraft centers that copied «Indian» rattle-mirrors
but in accordance with their industrial and artistic tradition.
Probably, in the 2—1 cent. BC. a kind of disk
with cones and rollers relief was taken by Lower Ob
population culture and had been reproduced on different
metal plates and buckles for a few more centuries.